Women's development: policy and administration - Varma, Sudhir (Jaipur, 1992)
The study is first of its kind in focus as well as in locus as an exploratory analysis into the impact of various policies and programmes on the three sub-themes-Health, Education and Employment-of the main theme Equality, Development and peace of the United Nations Decade for women 1975-85
Keywords: Women's right